MYRMECOFAUNA (HYMENOPTERA: FORMICIDAE) AS A BIOINDICATOR OF THE QUALITY OF SOILS SUBMITTED TO THE APPLICATION OF PIG FARMING WASTEWATER - Tessaro, Dinéia; Sampaio, Silvio César; Pocojeski, Elisandra (Scientia Agraria, 2017)
The structure of the communities of ants is of particular interest as bio indicators given their importance in environmental impact studies, as they present abundance and species richness, specialized taxa, wide geographical distribution, easily sampled in addition to being sensitive to environmental changes. Considering the above, the objective of this study was to evaluate the effects on the diversity of myrmecofauna through the application of pig farming wastewater (0, 100, 200 and 300 m3 ha-1) combined with nitrogen fertilization (0 and 100% of the recommended dose for culture) in typic dystroferric Red Latosol cultivated with baby corn. For evaluating the myrmecofauna, pitfall traps were installed and organisms classified in terms of gender. The Formicidae family had increased density to 200 m3 ha-1 doses of pig farming wastewater, but without showing changes due to chemical fertilization. However, sorting the gender taxonomic level showed no significant effects on different groups, except for the Solenopsis genus, when it was used doses of 0 and 300 m3 ha-1of pig farming wastewater.